Flexible and Innovative Learning Spaces: An Exploration of Parental Perspectives on Change, Consultation and Participation - Benade, L (SAGE Publications, 2021)
The role played by innovative educational environments to support learning for the 21st century has attracted the interest of the Organisation for Economic Cooperation and Development at the global governance level and at the national policy level internationally. This article draws on global, European and Australasian research and data from a qualitative study of consultation and participation in the development of innovative and flexible learning spaces in the New Zealand context. It focuses specifically on the role of parents, drawing data from relevant policies and documents, a parent questionnaire and interviews of parents, architects and Ministry of Education Delivery Managers, responsible for delivering large capital works projects. While the architect participants believe their bold designs are inspirational and promote new pedagogical styles, and positive relationships, some parents view these open-plan learning areas (and associated pedagogies) as needlessly experimental, placing the needs and education of their children at risk. Delivery Managers are focussed on seeing the projects to conclusion, on time and on budget. The critical analysis considers the findings in relation to the research question and reflects on the dual themes of innovation and risk. Further questions for research are suggested.
Keywords: Innovative learning environments; Parental participation; School architecture; Open-plan learning; Flexible learning Space